Numpy Library Capabilities. Vectorized Calculation In Numpy Va Type Of Information (Eurasian Research Bulletin, 2022)
The article shows the difference between vectorized and conventional in the NumPy library and clearly defining the type of data when creating data. In addition, other types of information are considered.